Pengaruh Katalis NiMo Terhadap Kualitas Minyak Batubara Hasil Pencairan Tidak Langsung - Rika Damayanti; Susila Arita R; Fitri Hadiah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
Coal is a fossil energy source that is widely used as a soild fuel in many sectors. The development of indirect coal liquefaction technology is one type of technology used to convert coal into a liquid fuel product in the form of coal oil with characteristics resemble petroleum fuels. Coal oil production can be an alternative fuel source for future energy needs. In this study, the indirect liquefaction process of coal (calorific value = 6400 kcal/kg) was done in the fluidized bed reactor by heating the reactor with an electric furnace, where the process took place at temperature 350oC - 500oC and the catalyst weight was varied into 0%, 5%, 10%, and 15%. Air with a flow rate 2 LPM is flowed during the process and the lenght of the process was 60 minutes. From this research, the best characteristics of coal oil produced at a temperature of 400oC - 450oC with a catalyst weight of 15%. The characteristics of the coal oil obtained have a density of 0.852 g / cm3, specific gravity of 0.853 and oAPI gravity of 34.41. The results of GC-MS analysis was known that 46.15% of the composition of hydrocarbons in coal oil is the fraction of gasoline.